Persistent sleep disturbance is associated with treatment response in adolescents with depression. (June 2013) - Manglick, Maneesha; Rajaratnam, Shantha M; Taffe, John; Tonge, Bruce; Melvin, Glenn
Background: Sleep disturbances are highly prevalent in adolescents with depressive disorders. To date there is limited evidence of the extent to which sleep disturbances are associated with treatment response in adolescents. This study aimed to examine the extent to which self-reported sleep disturbances are associated with treatment response in adolescents with depression. Method: Sleep data were gathered from a sample of 166 adolescents (aged 12–18 years) with a diagnosis of a DSM-IV depressive disorder who underwent 3 months of treatment (psychosocial and/or pharmacotherapy (sertraline)) in community-based research programs. The subjective report of sleep disturbance within depressive disorders was assessed using the Kiddie Schedule for Affective Disorders and Schizophrenia for School Age Children at three time points: pre-treatment, post-treatment and 6-month follow-up. Results: Sixty-nine percent of participants had a sleep disturbance pre-treatment and approximately 75% of these participants had threshold symptoms. Threshold sleep disturbances that persisted from pre- to post-treatment assessments were positively associated with depression at the 6-month follow-up. An ordered logistic regression model controlling for gender, treatment group and comorbid anxiety estimated a 70% risk of depression or partial remission for those with persistent sleep disturbance. Treatment group, anxiety and gender generally had no significant effect on the relationship between sleep and depression. Conclusion: Sleep disturbances were highly related to depressive state and were associated with poorer treatment response in adolescents with depression. These results provide a rationale for further exploration of sleep-related treatments for adolescents with depression. Knowledge of patient-reported persistent sleep disturbances can help clinicians to predict treatment outcomes and may direct them to augment treatment or focus on sleep-related treatment strategies.